Adapting a nurse-led primary care initiative to cardiovascular disease control in Ghana: a qualitative study - Leah A. Haykin; Jordan A. Francke; Aurelia Abapali; Elliasu Yakubu; Edith Dambayi; Elizabeth F. Jackson; Raymond Aborigo; Denis Awuni; Engelbert A. Nonterah; Abraham R. Oduro; Ayaga A. Bawah; James F. Phillips; et al. (BMC, 2020)
Abstract Background Cardiovascular Disease (CVD) is a growing cause of morbidity and mortality in Ghana, where rural primary health care is provided mainly by the Community-based Health Planning and Services (CHPS) initiative. CHPS locates nurses in community-level clinics for basic curative and preventive health services and provides home and outreach services. But CHPS currently lacks capacity to screen for or treat CVD and its risk factors. Methods In two rural districts, we conducted in-depth interviews with 21 nurses and 10 nurse supervisors to identify factors constraining or facilitating CVD screening and treatment. Audio recordings were transcribed, coded for content, and analyzed for key themes. Results Respondents emphasized three themes: community demand for CVD care; community access to CVD care; and provider capacity to render CVD care. Nurses and supervisors noted that community members were often unaware of CVD, despite high reported prevalence of risk factors. Community members were unable to travel for care or afford treatment once diagnosed. Nurses lacked relevant training and medications for treating conditions such as hypertension. Respondents recognized the importance of CVD care, expressed interest in acquiring further training, and emphasized the need to improve ancillary support for primary care operations. Conclusions CHPS staff expressed multiple constraints to CVD care, but also cited actions to address them: CVD-focused training, provision of essential equipment and pharmaceuticals, community education campaigns, and referral and outreach transportation equipment. Results attest to the need for trial of these interventions to assess their impact on CVD risk factors such as hypertension, depression, and alcohol abuse.